1986
DOI: 10.1177/0148607186010005522
|View full text |Cite
|
Sign up to set email alerts
|

Nutrition Education in Schools of Nursing in the United States. Part 1. The Evolution of Nutrition Education in Schools of Nursing

Abstract: In 1981 the Nurses' Committee of the American Society for Parenteral and Enteral Nutrition appointed an Ad Hoc Committee to investigate the evolution of and the current status of nutrition education curriculum in schools of nursing accredited by the National League for Nursing. This investigation identified current trends in the teaching of nutrition content in baccalaureate and graduate schools of nursing. Part one explores the evolution of nutrition content in school of nursing curriculum; while part two (to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

1995
1995
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…An attempt to compare the nutritional con tent of curricula taught to professionals here in Kuwait and in other parts of the world revealed that few studies are available regard ing dental [22] and nursing [23,24] curricula and nothing was available on KG curriculum. As early as 1981, efforts were directed to wards investigating the status of nutrition education curricula in schools of nursing ac credited by the National League [23], To date, questions related to the nutrition content that should be emphasized in the nursing program, its proper placement, and the best way to teach it.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An attempt to compare the nutritional con tent of curricula taught to professionals here in Kuwait and in other parts of the world revealed that few studies are available regard ing dental [22] and nursing [23,24] curricula and nothing was available on KG curriculum. As early as 1981, efforts were directed to wards investigating the status of nutrition education curricula in schools of nursing ac credited by the National League [23], To date, questions related to the nutrition content that should be emphasized in the nursing program, its proper placement, and the best way to teach it.…”
Section: Discussionmentioning
confidence: 99%
“…As early as 1981, efforts were directed to wards investigating the status of nutrition education curricula in schools of nursing ac credited by the National League [23], To date, questions related to the nutrition content that should be emphasized in the nursing program, its proper placement, and the best way to teach it. have not been answered [24].…”
Section: Discussionmentioning
confidence: 99%
“…The expansion period (2000–2015) highlights the contributions of NSN to expanding the science and practice of nutrition care to the discipline of nursing (including general and specialty nursing practice) and beyond. Key events are highlighted in the chronology in Table 1 2 – 15 . The American Society for Parenteral and Enteral Nutrition (ASPEN) has served as the professional home for NSN since 1976.…”
Section: Chronology Of Nutrition Support Nursing 1854–2016mentioning
confidence: 99%
“…Unfortunately, nutrition curricula education in nursing schools have not been examined since the early 1990's and that information is now outdated [39][40][41]. Formal evaluations of nutrition education methods in nursing schools are also dated [42].When considering the nutrition continuing education needs of practicing nurses, the literature is equally limited and the papers reflect only international nursing practice [43][44][45].…”
Section: Prioritizing Malnutrition Screening and Intervention Within mentioning
confidence: 99%